2013
DOI: 10.1016/j.ygyno.2013.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence patterns after extended treatment with bevacizumab for ovarian, fallopian tube, and primary peritoneal cancers

Abstract: Objective To evaluate patterns of recurrence for ovarian, fallopian tube, and primary peritoneal cancer patients undergoing extended treatment with bevacizumab (BEV). Methods A retrospective review of patients with primary ovarian, fallopian tube, or peritoneal cancer treated with BEV alone or in combination with other chemotherapy from 2001 to 2011 was performed. Qualified patients were identified by chemotherapy records. Electronic medical records, labs, and imaging reports were reviewed and abstracted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The weaknesses of the investigation are represented by its retrospective nature, by the lack of randomization in the criteria of choice for first-line carboplatin/paclitaxel-based chemotherapy with or without bevacizumab, by the higher incidence of some favorable prognostic variables (younger age, better PS and longer time to recurrence) in patients who received bevacizumab in firstline treatment, and by the addition of bevacizumab to second-line chemotherapy in 3.6% and 19.5%, respectively, of the patients previously treated and not treated with this antiangiogenic agent. In any case, in agreement with the pooled analysis of Miles et al (37), the present investigation on patients with advanced epithelial ovarian cancer found no significance difference in both the sites of recurrence and the clinical outcome between complete responders who recurred after first-line chemotherapy plus bevacizumab and complete responders who recurred after first-line chemotherapy alone. Therefore, these results failed to detect a more aggressive behavior of recurrent epithelial ovarian cancer after bevacizumab-containing primary treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The weaknesses of the investigation are represented by its retrospective nature, by the lack of randomization in the criteria of choice for first-line carboplatin/paclitaxel-based chemotherapy with or without bevacizumab, by the higher incidence of some favorable prognostic variables (younger age, better PS and longer time to recurrence) in patients who received bevacizumab in firstline treatment, and by the addition of bevacizumab to second-line chemotherapy in 3.6% and 19.5%, respectively, of the patients previously treated and not treated with this antiangiogenic agent. In any case, in agreement with the pooled analysis of Miles et al (37), the present investigation on patients with advanced epithelial ovarian cancer found no significance difference in both the sites of recurrence and the clinical outcome between complete responders who recurred after first-line chemotherapy plus bevacizumab and complete responders who recurred after first-line chemotherapy alone. Therefore, these results failed to detect a more aggressive behavior of recurrent epithelial ovarian cancer after bevacizumab-containing primary treatment.…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective review of 89 patients with epithelial ovarian cancer treated with bevacizumab alone or in combination with other chemotherapy agents, has shown that the patients who received more than 12 cycles of bevacizumab were more likely to recur in extra-visceral sites (p=0.04), especially in lymph nodes (p=0.0002), compared with those who received ≤12 cycles, thus suggesting that the extended treatment with this antiangiogenic agent might alter the pattern of recurrence (36). Miles et al (37) have performed a pooled analysis of five randomized, placebocontrolled trials enrolling 4,205 patients with breast, colorectal, renal, and pancreatic cancer to assess whether the discontinuation of bevacizumab was associated with accelerated disease progression or increased mortality. They found that the median time from the discontinuation of bevacizumab/placebo as a result of an adverse event to progression or death was 4.0 months [95% confidence interval (CI)=3.4-4.6 months] for bevacizumab and 3 months (95%CI=2.6-3.8 months) for placebo [hazard ratio (HR)= 0.93; 95%CI=0.79-1.10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, peritoneal recurrence described as diffuse disease was also more frequent in patients treated in the first line by bevacizumab (96.8%) compared to the chemotherapy group [ 109 ]. The results of the study were consistent with previous study conducted by Dao et al which showed, that patients treated with bevacizumab in the first line had a higher probability to recur in extra-visceral sites ( p = 0.04) or in lymph nodes, especially those located extraperitoneally ( p = 0.0002) [ 110 ]. In the comparison, the study by Kim et al performed on the group of 52 patients with epithelial ovarian cancer treated by platinum-based doublet chemotherapy with bevacizumab as a second-line treatment and 104 patients in the control group only treated by chemotherapy did not show the same dependence.…”
Section: Bevacizumab In Recurrent Ovarian Cancer Potential Impact Of ...supporting
confidence: 91%
“…The mechanism of ovarian cancer resistance involves a variety of genes and a number of different signaling pathways, including the following aspects: Affecting the effective concentration of intracellular changes, including the multidrug resistance gene; expression of the multidrug resistance protein; expression of the lung resistance associated protein ( 19 , 20 ) and affecting drug targets, including β-tubulin expression changes, the cytoskeleton protein gene and the abnormal expression of compartment of uncoupling receptor and ligand ( 21 ); DNA damage repair abnormalities, including DNA mismatch repair gene, topoisomerase gene and other changes in the levels of expression or interaction abnormalities ( 22 , 23 ); apoptosis-associated genes, including TP53, survivin, caspase, B cell lymphoma 2, and other gene regulation abnormalities associated with resistance to ovarian cancer ( 24 , 25 ). Although, targeted drugs have been developed in response to a number of the aforementioned mechanisms ( 26 , 27 ), they do not induce a fundamental change in the resistance to ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%